A united credible capacity evaluation method of distributed generation and energy storage based on active island operation - Jiahao, Chen; Bing, Sun; Yuan, Zeng; Ruipeng, Jing; Yunfei, Li; Shiqian, Ma (Frontiers in Energy Research, 2023)
Cooperating with distributed energy storage (ES), distributed generation (DG) is with the potential of supply load stably under both normal and failure period of distribution network. Therefore, DG has not only electricity value, but also capacity value. The capacity value can be characterized by credible capacity (CC) index. However, the uncertainty of DG output and the sequential characteristics of ES operation must be considered during united CC evaluation. A united CC evaluation method of DG and ES based on active island operation is proposed. The proposed method carries out day ahead economic dispatching under normal state and island partition under fault state alternately to realize accurate reliability calculation, which is the key link of CC searching. The main work are as follows. Firstly, a day ahead economic dispatching model under normal state is established to obtain the sequential remaining electricity information of ES. Secondly, the models of maximum island partition (MIP) and optimal island rectification (OPR) are established based on electricity sufficiency and power balance information. By solving MIP and OPR models alternately, optimal island partition schemes under fault state could be achieved. Then, convergence criterion based on variance coefficient instead of artificial selection is designed in reliability calculation. Finally, the united CC of DG and ES is evaluated in the PG&E 69-bus system. It is found that CC value increases by 23%, 53% and 61% respectively under the ES allocation ratio of 20%, 30% and 40%. It can be seen that the integration of ES makes a significant impact on DG CC value.